Isoglossa darbyshirei (Acanthaceae), a new plietesial species from the Albertine Rift (Rwanda, Burundi) - Champluvier, Dominique; Fischer, Eberhard (Phytotaxa, 2020)
Isoglossa darbyshirei is described as a new species from Rwanda and Burundi. Its affinities to I. humbertii and I. laxiflora are discussed. Based on current knowledge I. darbyshirei is given a preliminary conservation assessment of Vulnerable (VU B2). The new species shows a plietesial life cycle that is briefly discussed. A key to the Isoglossa laxiflora-group is also provided.